SYSTEMIC AND EPISTEMOLOGICAL FACTORS IN ACADEMIC ACHIEVEMENT (Journal of Namibian Studies : History Politics Culture, 2023)
Due to the COVID 2019 pandemic, the Peruvian Ministry of Education establishes the provision of education services in the distance modality. In this sense, the present research allows identifying the systemic and epistemological factors that influence the academic performance of 198 students of the School of Engineering of the Professional School of Systems and Computing of the Universidad Peruana Los Andes. The methodology used to obtain the data consisted in the application of Martha Artunduaga's instrument on Variables that influence academic performance at the University; likewise, the Epistemological Beliefs questionnaire adapted by Di Matteo from Scrommer's questionnaire was applied. It is concluded that there is influence of systemic factors with sociocultural, demographic, institutional, pedagogical, cognitive and attitudinal variables, all of which are interrelated to determine academic performance; likewise, there is influence of epistemological factors with 4 dimensions, simple knowledge, certain knowledge, fixed ability and fast learning. From the results, 47.5% of the students indicate that their academic performance has been good, and 45% regular; 65% of the students feel moderately satisfied with factors related to the university and the way the teaching-learning process is taught; in relation to epistemological beliefs and academic performance it is concluded that both maintain weak correlations according to Spearman's coefficient.